Evaluation of Two Beta-Tricalcium Phosphates with Different Particle Dimensions in Human Maxillary Sinus Floor Elevation: A Prospective, Randomized Clinical Trial - Mendes, Bruno Coelho [UNESP]; Pereira, Rodrigo Dos Santos; Mourão, Carlos Fernando de Almeida Barros; Montemezzi, Pietro; Santos, Anderson Maikon de Souza [UNESP]; Moreno, Jéssica Monique Lopes [UNESP]; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (MDPI, 2022)
This study aimed to compare two beta-tricalcium phosphates with different particle sizes in human maxillary sinuses lifting. The immunolabeling of cells for RUNX2 and VEGF were performed to evaluate the osteoblast precursor cells and the vascular formation after 6 months of bone repair. Ten maxillary sinuses were grafted with autogenous bone graft (Group 1), 10 were grafted with ChronOs® (Group 2), and 10 were grafted with BETA-TCP® (Group 3). After 6 months of bone healing, biopsies were obtained to assess the new bone formed by histomorphometric and immunohistochemical evaluation for RUNX2 and VEGF. The mean bone formation for Group 1 was 51.4 ± 17.4%. Group 2 presented 45.5 ± 9.9%, and Group 3 conferred 35.4 ± 8.0% of new bone formation. The RUNX2 offered low for Groups 1 and 2 with high cellular activity for osteoblast in Group 3. The VEGF immunolabeling was moderate for Groups 1 and 2 and intense for Group 3. In conclusion, it was possible to show that the bone substitutes evaluated in the present study presented suitable outcomes for bone regeneration, being an alternative for the autogenous bone graft in maxillary sinus bone height reconstruction.
Keywords: Biomaterials; Bone substitutes; Sinus floor augmentation